Extraction of tritium from spherical granules at the expense of kickback - Kuikabaeva, A.; Beckman, I.; Tazhibaeva, I.; Suleimenov, A. (Recent Contributions to Physics, 2015)
The analysis of selection of tritium is conducted from a spherical granule, were figured on runs of return tritium atoms  in titanate of lithium and in the atmosphere of helium. In the model of selection the atoms of return generated in a nuclear reaction it was succeeded to expect the stake of atoms of tritium abandoning a sphere (granule) due to the  effect of return. It was also succeeded to build a concentration profile, taking into account impoverishment of surface  of sphere by tritium, necessary for the exact calculation of kinetics of selection of tritium from a spherical standard.
Keywords: thermonuclear reactor, excretion of tritium, blanket, spherical granule, recoil effect